2013
DOI: 10.4236/cs.2013.47059
|View full text |Cite
|
Sign up to set email alerts
|

High Accurate Howland Current Source: Output Constraints Analysis

Abstract: Howland circuits have been widely used as powerful source for exciting tissue over a wide frequency range. When a Howland source is designed, the components are chosen so that the designed source has the desired characteristics. However, the operational amplifier limitations and resistor tolerances cause undesired behaviors. This work proposes to take into account the influence of the random distribution of the resistors in the modified Howland circuit over the frequency range of 10 Hz to 10 MHz. Both output c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…Acceptable results by Macias et al [12] were found in the AFE-1 topology when assessing the circuit performance up to 1 MHz. The AFE-2 topology has a good stability for the frequency range used in this work, but depends strongly on the symmetry between the current sources [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acceptable results by Macias et al [12] were found in the AFE-1 topology when assessing the circuit performance up to 1 MHz. The AFE-2 topology has a good stability for the frequency range used in this work, but depends strongly on the symmetry between the current sources [13].…”
Section: Discussionmentioning
confidence: 99%
“…The VCCS provides a constant output current (=1 mApp) that is given by the ratio between V out (=1 Vpp) and the resistor r (=1 kΩ). All resistors have a low precision tolerance (±1%) in order to obtain a good current source performance [13]. In order to reduce power consumption, the resistor r of the Howland circuit (see Figure 3) should be much smaller than the value of R (=47 kΩ).…”
Section: Mirrored Modified Howland Current Source -Afe-2mentioning
confidence: 99%
“…The design of an appropriate VCCS is one of the most challenging parts in an EIT system design, since the specifications must satisfy high output impedance z out , Common Mode Rejection Ratio (CMRR) and sufficient current amplitude (low enough for the patients' safety and high enough to avoid notable noise rates) for as high frequency range as possible. In this study the topologies simulated are based on the modified Howland current source, described in [14,20,21]. Specifically, two main approaches have been tested: (a) the grounded load and (b) the mirrored modified Howland VCCS [20].…”
Section: Voltage-to-current Conversionmentioning
confidence: 99%
“…In this study the topologies simulated are based on the modified Howland current source, described in [14,20,21]. Specifically, two main approaches have been tested: (a) the grounded load and (b) the mirrored modified Howland VCCS [20]. Their topologies are shown in Figure 1b,c correspondingly.…”
Section: Voltage-to-current Conversionmentioning
confidence: 99%
“…First is an AC current source, which must be stable within working frequency range; second is a data acquisition system to record voltage, current, and their phase difference; and third is software for computing and displaying the impedance dispersion curves, which is commonly in the Bode plot or Nyquist plot.Furthermore, in an effort to provide a BIS instrumentation system in good performance, some researchers have offered the new design. Starting from precision AC current sources [26], the high accuracy data acquisition system [27,28], even the whole system device [29][30][31][32][33]. Commonly, the offered BIS instrumentation system is arranged in modular and work separately.…”
mentioning
confidence: 99%